Genome-wide association study identifies multiple susceptibility loci for craniofacial microsomia - Yong-Biao Zhang (Nature Communications, 2016)
Craniofacial microsomia is a congenital anomaly that affects the development of the skull. Here, the authors perform a genome-wide association study on patients in China and identify particular loci that provide insights into genetic mechanisms.